ANALISIS PENGARUH SIZE, ROA, FDR, NPF DAN BOPO TERHADAP CAPITAL ADEQUACY RATIO PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2010-2014 - Oktaviana, Rheza; Syaichu, Muhammad (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to analyze the influence of Size, Return On Asset (ROA), Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), and Operating Expenses Operating Income (BOPO) to Capital Adequacy Ratio (CAR). Case study on Indonesian Islamic banks in 2010-2014.The number of sample used in this research were 11 banks. Secondary data were obtained from financial statements can be downloaded from the official website of each bank and the official website of Bank Indonesia covering the period of 2010 until the end of 2014. The analytical method used in this research is Multiple Linear Regression Analysis where previously performed classical assumption that includes Normality Test, Multicollinearity Test, Autocorellation Test, and Heteroskedastisitas Test with a significance level of 5%. The study found that Financing to Deposits Ratio (FDR) is positively significant influenced to Capital Adequacy Ratio (CAR). Meanwhile, Size and Non Performing Financing (NPF) are significant but negatively influenced to the Capital Adequacy Ratio (CAR). On the other hand, Return On Assets (ROA) and Operating Expenses Operating Income (BOPO) have no significant effect on capital adequacy of Indonesian Islamic bank. Based on the coefficient determination, variable Size, Return On Asset (ROA), Financing to Deposits Ratio (FDR), Non Performing Financing (NPF), and Operating Expenses Operating Income (BOPO) have 64,3% effect against Capital Adequacy Ratio (CAR). While the remaining 35,7% is influenced by other variables that are not used in this study.